A Question of Belief: An Analysis of Item Content in Paranormal Belief Questionnaires - Storm, Lance (Journal of Scientific Exploration, 2017)
This study examined the degree to which paranormal believers, who profess ‘strong’ belief in the popular expression of a topic known as the primary item (e.g., There is such a thing as extrasensory perception), disagree with related items and/or the putative ‘cause’ of the topic, known as secondary items (e.g., Some people have an unexplained ability to predict the future). It was theorised that scoring differences between primary and secondary items might indicate certain kinds of paranormal believer, which might then allow us to conduct deeper analyses of paranormal belief (PB) and its putative relationships with deficits and dysfunctions. A complete set of items drawn from ten extant PB scales was administered to a sample of 343 respondents. Using Factor Analysis, we developed the Paranormal Belief Informedness Scale (PBIS), consisting of 10 primary items, and 10 secondary items, scores of which were used to identify three major PB types from a sample of 343 respondents: ‘primary believers’ (who believe in all 10 primary items, and thus exhibit ‘strong’ PB), ‘primary non-believers’ (who believe in none of the 10 primary items), and ‘mixed believers’ (who believe in only some primary items). We found significant response-rate differences between primary and secondary items across believer types, and across psi categories (i.e., extra-sensory perception, psychokinesis, and life after death). For the full sample, it was shown that there is a significant relationship between PB and reality testing deficits as measured on the reality testing subscale of the Inventory of Personality Organisation (IPO-RT; Lenzenweger et al., 2001). However, this relationship tended not to be significant across believer types. Also, there was no evidence in the full sample, or in any believer type, that PB was correlated with depression as measured on the Beck Depression Inventory (BDI-II). We suggest that such relationships are not necessarily linear but may only be monotonic, and researchers need to give attention to possible ‘ceiling effects’ rather than assume that a significant outcome implies a trend across all levels of paranormal belief.